2016
DOI: 10.1371/journal.pone.0156528
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Morpho-Agronomical Characterization of Root Architecture at Seedling and Reproductive Stages for Drought Tolerance in Wheat

Abstract: Water availability is a major limiting factor for wheat (Triticum aestivum L.) production in rain-fed agricultural systems worldwide. Root architecture is important for water and nutrition acquisition for all crops, including wheat. A set of 158 diverse wheat genotypes of Australian (72) and Indian (86) origin were studied for morpho-agronomical traits in field under irrigated and drought stress conditions during 2010–11 and 2011-12.Out of these 31 Indian wheat genotypes comprising 28 hexaploid (Triticum aesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…Hence, divergent parents selected from these clusters can be utilized in breeding program for barley improvement under rain-fed conditions, which is the main breeding target in India. Present results are in congruence with Tomar et al (2016) and Huang et al (2017), who also categorized genotypes into highly tolerant, sensitive, moderately sensitive and tolerant while studying molecular and agro-morphological characterisation of root architecture for drought tolerance in wheat and Eruca, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Hence, divergent parents selected from these clusters can be utilized in breeding program for barley improvement under rain-fed conditions, which is the main breeding target in India. Present results are in congruence with Tomar et al (2016) and Huang et al (2017), who also categorized genotypes into highly tolerant, sensitive, moderately sensitive and tolerant while studying molecular and agro-morphological characterisation of root architecture for drought tolerance in wheat and Eruca, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Information on cowpea drought tolerance at the seedling stage would be substantial in efforts toward developing drought-tolerant cultivars. Tomar et al (2016) showed that plants with good tolerance at early vegetative growth were able to withstand drought stress at a later stage of plant development. Another study demonstrated that plant genotypes with some degree of drought tolerance at the seedling stage were likely to be drought tolerant at later stages (Rzepka-Plevne s et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, incorporating selection for root traits directly in a breeding program has been met with many challenges, foremost the difficulty of phenotyping large numbers of genotypes in a cost-and time-efficient manner (Mace et al, 2012). Several wheat studies have evaluated roots using different phenotyping methods including rhizotrons (Nagel et al, 2012;Lobet and Draye, 2013;Clarke et al, 2017), soil coring (Trachsel et al, 2011;Wasson et al, 2012;Wasson et al, 2014), lysimeters (Ehdaie et al, 2014;Elazab et al, 2016), hydroponics (Liu et al, 2015), paper roll culture and Petri dishes for seedling (Tomar et al, 2016), rhizoboxes (Fang et al, 2017, and X-ray-computed tomography (Gregory et al, 2003;Mairhofer et al, 2013;Colombi and Walter, 2017;Flavel et al, 2017). However, most of these techniques are either expensive or not precise enough and reproducible.…”
Section: Root System Architecture and Its Association With Yield Undementioning
confidence: 99%